PENINGKATKAN KEMAMPUAN BERHITUNG PERMULAAN ANAK USIA 4-5 TAHUN MELALUI MEDIA PERMAINAN STICK ANGKA - Apriyansyah, Chandra - (Universitas sriwijaya, 2018)
This study aims to obtain data on improving early numeracy skills of children aged 4-5 years through the media game stick figures. The research was conducted in PAUD Mawar Rempoa, East Ciputat with the subject of the research is the children of PAUD Mawar Rempoa, East Ciputat Group A with the number of 10 children in the 2015/2016 Lesson Year. The research method used using the cycle model developed by Kemmis and Mc. Taggart. Classroom Action Research is done through the following stages: planning, action execution, monitoring / observation, and reflection. Target achievement in this research is 80%. This study has obtained results indicating an increase in numerical ability seen from the percentage data in each cycle. Counting ability of 10 children, on pre cycle of percentage value of child 42,6% and value of indicator percentage 41,4%. While in cycle I the value of children and the percentage of indicators increased to 71.4%.hen on the second cycle increased again to 91.4% and also indicators. Based on the description, it can be concluded that by using the media game stick figures can improve the ability of counting group A students in PAUD Mawar Rempoa, East Ciputat can be said successful.